Pituitary Macroadenoma on a Patient with Headache and a Third Cranial Nerve Paralysis (Revista de Medicina Clinica, 2024)
Pituitary macroadenomas represent a small percentage of sellar masses. The clinical manifestations are secondary to the hormonal alterations that they produce and/or to the compression of adjacent structures. The most frequent associated neurological deficit is bitemporal homonymous hemianopsia, with the possibility of manifesting oculomotor nerve palsy in less frequent cases. We present the case of a patient with a pituitary macroadenoma with the main clinical manifestation of paresis of the third cranial nerve initially oriented as a circle of Willis aneurysm.
Keywords: Pituitary macroadenoma; Oculomotor nerve; Palpebral ptosis; Hypopituitarism